Kolaborasi Pencegahan dan Pemberantasan Narkotika: Studi Kasus Badan Narkotika Nasional Kota Surakarta - Hermoyo, Bambang; Werdani, Vidya Dyah; Hartanto, Yudha Hendra; Kinaryosi, Azahra; Pardosi, Frankey Caisario; Aundrianagari, Firstanya Lazca (Journal of Contemporary Law Studies, 2024)
The aim of this study is to evaluate the efforts undertaken by the Surakarta City National Narcotics Agency (BNNK Surakarta) in preventing and combating the abuse and trafficking of narcotics. The methodology involved the analysis of secondary data from BNNK Surakarta activity reports, interviews with relevant personnel, and surveys among the local community. The findings indicate that the collaboration between BNNK Surakarta, the Surakarta Police Narcotics Research Unit, and several anti-drug forums and communities has successfully implemented comprehensive, integrated, and multidimensional prevention methods. However, challenges persist in law enforcement, therapy, and rehabilitation of narcotics victims. The conclusion emphasizes the importance of collective action among various stakeholders in the efforts to prevent and combat the abuse and trafficking of narcotics. With improved cooperation, it is hoped that the Surakarta community can be freed from narcotics-related cases and create a productive, healthy, and competitive environment.